Over her shoulder: What are women’s relationship perceptions when there has been lived experience of domestic violence within that relationship? - Hannan, Amy (2015)
Research into the social phenomena of domestic violence is a relatively new area of exploration. The focus for domestic violence researchers has been across a broad range of topics with a key theme being the reasons that women stay or leave the relationship. The study described in this thesis engaged with women in discussions regarding their perception of their relationship when there had been experiences of domestic violence. The methodology included the use of a focus group with three women from the South West of Western Australia. The focus group consisted of both individual and group sessions. For the focus group, word association and brainstorming were tools used to enable deep reaching, in-depth discussion that produced rich data. Data was thematically analysed using a process of coding. The analysis found a number of themes present, of which, four thematic chapters were developed. The findings of this study have implications for how the realities of domestic violence are understood by the greater community, and how services engage with women who have been subjected to abuse